The effect of kinesiophobia on physical activity, balance, and fear of falling in patients with Parkinson's disease - POLAT, MİNE GÜLDEN; OĞUZ, SEMRA (TAYLOR & FRANCIS INC, 2022)
Purpose Kinesiophobia is defined as the fear of movement and activity resulting from a feeling of vulnerability to painful injury or re-injury. This study aimed to determine the effect of kinesiophobia on physical activity, balance, and fear of falling in patients with Parkinson's disease. Methods The study, which was designed as a cross-sectional type, was conducted with 86 patients with Parkinson's disease (age 61.25 SD [9.72] years old) by face-to-face interviews with the patients. The Tampa Scale of Kinesiophobia, International Physical Activity Questionnaire-Short Form, Berg Balance Scale, Falls Efficacy Scale, Visual Analog Scale - Fear of Falling, Unified Parkinson's Disease Rating Scale - motor score, and the Hoehn and Yahr scale were used to evaluate the patients. Results Patients with Parkinson's disease who had high levels of kinesiophobia had lower levels of physical activity, worse balance, and higher disease severity and fear of falling. A correlation was found between the Tampa Scale score and physical activity, balance, fear of falling, falls efficacy, and disease motor score (p r = -0.38, -0.54, 0.67, 0.57, and 0.37, respectively). According to multiple linear regression analysis, kinesiophobia explained the dependent variables to varying degrees ranging from 13% to 44% (p < .001). Conclusions Patients with Parkinson's disease may have kinesiophobia. Rehabilitation programs to support functional capacity for these patients should be developed considering the presence of kinesiophobia.
Keywords: Balance; fear of falling; kinesiophobia; Parkinson's disease; physical activity; QUALITY-OF-LIFE; RELIABILITY; VALIDITY; PEOPLE; SCALE; EFFICACY; ADULTS